The scientific construction of copyright in Europe: Copyright as a Common European Institution. (Revista de Estudios Europeos, 2026)
Since the 18th century copyright has undergone significant evolution in Europe influenced by the Enlightenment and the expansion of the printing press. Although each country has developed its own regulations, there exists a common foundation of principles that have contributed to the consolidation of copyright as a genuinely European institution. This paper analyses the changes that have transcended national borders and fostered a framework for the protection of intellectual property, with a shared identity that guides the safeguarding of artistic creation, regardless of the intelligence behind it, whether human or artificial.
Keywords: Intellectual property; Copyright; History of Intellectual Property; Evolution of copyright in Europe; Protected works under copyright